Penggunaan Metode Pembelajaran Index Card Match dalam Meningkatkan Motivasi Dan Hasil Belajar Siswa Pada Mata Pelajaran Aqidah Akhlak Kelas IX A di MTSN 2 Kabupaten Probolinggo Tahun 2021/2022 - Sugianto, Muhammad; Wiranti , Anggraeni Dwi (LP3M UNZAH GENGGONG, 2022)
Abstract This study aims to determine the motivation and learning outcomes of students in class IX A MtsN 2 Probolinggo Regency using the Index Card Math method in the Akidah Akhlak subject. This research is a classroom action research. The population of this study were 24 class IX A MTsN 2 Probolinggo students. The purpose of this study is to find out how the Index Card Match method around the material of aqidah morals can increase the motivation and learning outcomes of class IX A students at MTSN 2 Probolinggo Regency and to find out whether the application of the Index Card Match Method can increase student motivation in class aqidah morals material. IX A at MTSN 2, Probolinggo Regency. Data collection techniques used are questionnaires, observations, interviews and documents. The questionnaire was conducted to get students' learning motivation. Documents carried out in the use of this method are expected to obtain a meaning that is more valid in truth. The data analysis technique used is a quantitative approach. Score criteria are stated on a low, medium and high scale. Student learning outcomes are declared complete if they meet the KKM with a score of 70. The results show that through the application of the Index Card Match method, student learning outcomes increase from pre-cycle, cycle 1 and cycle 2. Research results from cycle 1 and cycle II Based on the results of students' daily journals, obtained an average positive response of students to learning using Index Card Match 100%. And the average student points in learning above, it can be concluded that student participation in learning is very high. In cycle I, the average point of 91.03 rose to 95.86 in cycle II. Then it can be concluded that the success of learning using the Index Card Match method. Keywords: Index Card Match, Student Learning Motivation, Learning Outcomes of Aqidah Akhlak Subject